Broadening the pore size of coal-based activated carbon via a washing-free chem-physical activation method for high-capacity dye adsorption. Issue 26 (18th April 2018) - Li, Longxin; Sun, Fei; Gao, Jihui; Wang, Lijie; Pi, Xinxin; Zhao, Guangbo
Abstract : Aiming to overcome the limitations of the narrow pore size distributions of traditional activated carbon, we demonstrate a new type of activated carbon with a broadened pore size distribution for high-rate and high-capacity aqueous dye adsorption. Abstract : Aiming to overcome the limitations of the narrow pore size distributions of traditional activated carbon materials and to achieve wide adaptabilities towards large molecules adsorption, we herein demonstrate a new type of activated carbon with a broadened pore size distribution for high-rate and high-capacity aqueous dye molecule (Rhodamine B) adsorption. The preparation of CP-AC is achieved by a facile and one-step mineral-assisted chem-physical activation strategy from Chinese large-reserve Zhundong coal with ZnCl2 and CO2 as the activation agents. The method yields the activated carbon (CP-AC) that has a pore-size broadened hierarchical pore configuration with a high surface area and a large pore volume, favorably enabling a high-capacity Rhodamine B adsorption up to 881 mg g −1, which is among the highest levels of the reported activated carbons. A sonication-assisted adsorption test further demonstrates the high-rate adsorption capability of CP-AC with Rhodamine B adsorption capacity up to 842 mg g −1 within 30 min (96% of the saturation capacity) while microporous activated carbon obtained by solely ZnCl2 activation could just achieve a capacity of 374 mg g −1 within 30 min. In virtue of the low-cost resource materials and washing-free craft, this work offers a simple and green preparation strategy towards high-performance coal based activated carbons, holding great potentials for the industrial production and applications.